Pengaruh metode dan motivasi belajar terhadap hasil belajar keterampilan lompat jauh - Syahruddin, Syahruddin (Universitas Nusantara PGRI Kediri, 2022)
The results of learning physical education skills were not limited to physical development but also mental development and motivation to learn. The purpose of this study was to determine the effect of the block method (BM) and the play-based random method (RM) on long jump skills (JLS) in terms of motivation (MTV). This type of research is quasi-experimental with a 2x2 factorial design. A sample of 20 Samiun Makassar public primary school students was randomly selected and divided into four groups. Treatment research for eight weeks. Before treatment, the sample was divided into two, high motivation (MTVH) and low motivation (MTVL), through questionnaires and the final test of long jump skills learning outcomes (JLS). The results showed that BM significantly increased JLS compared to RM (P<0.05). There was a significant interaction between Mt and MTV (P<0.05). The MTVH student group using MBB1 had better JLS than MRB1 (P<0.05). The group of students who had MTVL had no difference in results between MBB2 and MRB2 (P>0.05). KLJ in physical education for elementary school students is very good at using MB, and the teacher increases MTV during learning.